Exchange Rate Volatility and Pass-Through to Inflation in South Africa - Miyajima, Ken (IMF Working Papers; Working Paper ;, 2019)
Does the South African rand's relatively large volatility affect inflation? To shed some light on this question, a standard estimation technique of exchange rate pass-through to inflation is extended to incorporate exchange rate volatility. Estimated results suggest that higher exchange rate volatility tends to increase core inflation but to a relatively limited extent in South Africa. The finding lends support to the policy of allowing the rand to float freely and work as a shock absorber, consistent with the nation's successful inflation targeting regime.